The Larkins. Series 2 [videorecording (DVD)] - Nye, Simon, 1958-; Wilson, Abigail (Screenwriter); Walsh, Bradley, 1960-; Scalan, Joanna; Rae, Joelle; Stephen, Tok; Page, Lydia; Bates, H. E. (Herbert Ernest), 1905-1974 (Acorn, 2023)
When Pop sells the crumbling mansion next door to waspish newcomers for more than it's worth, he celebrates with plans to build a swimming pool but his neighbors soon plot their revenge. Can the Larkin clan keep him out of prison?